A Cell‐Free Platform Based on Nisin Biosynthesis for Discovering Novel Lanthipeptides and Guiding their Overproduction In Vivo. Issue 17 (21st July 2020) - Liu, Ran; Zhang, Yuchen; Zhai, Guoqing; Fu, Shuai; Xia, Yao; Hu, Ben; Cai, Xuan; Zhang, Yan; Li, Yan; Deng, Zixin; Liu, Tiangang
Abstract: Lanthipeptides have extensive therapeutic and industrial applications. However, because many are bactericidal, traditional in vivo platforms are limited in their capacity to discover and mass produce novel lanthipeptides as bacterial organisms are often critical components in these systems. Herein, the development of a cell‐free protein synthesis (CFPS) platform that enables rapid genome mining, screening, and guided overproduction of lanthipeptides in vivo is described. For proof‐of‐concept studies, a type I lanthipeptide, nisin, is selected. Four novel lanthipeptides with antibacterial activity are identified among all nisin analogs in the National Center for Biotechnology Information (NCBI) database in a single day. Further, the CFPS platform is coupled with a screening assay for anti‐gram‐negative bacteria growth, resulting in the identification of a potent nisin mutant, M5. The titers of nisin and the nisin analog are found to be improved with CFPS platform guidance. Owing to the similarities in biosynthesis, the CFPS platform is broadly applicable to other lanthipeptides, thereby providing a universal method for lanthipeptide discovery and overproduction. Abstract : The development of a cell‐free protein synthesis (CFPS) platform is described for rapid genome mining, screening, and the guiding overproduction of lanthipeptides in vivo. The functionality of the CFPS platform is demonstrated by using nisin (a typical lanthipeptide) for proof‐of‐concept studies. This CFPS platform provides a universal method for lanthipeptide discovery and overproduction.